Hubungan Dukungan Keluarga Dengan Tingkat Kekambuhan Penderita Skizofrenia di Kecamatan Kaliwungu Kabupaten Semarang - Wisnu Adi Prsityantama; Yulius Yusak Ranimpi (Program Studi S1 Keperawatan Universitas Ngudi Waluyo, 2018)
Family is the main supporter in the healing process of schizophrenic patients to prevent recurrence. In nursing care, family support is very important to play a role in preventing recurrence. Family attitudes that do not support the treatment of schizophrenia will make more frequent recurrence. This study aims to identify and quantify the relationship of family support and relapse in patients with schizophrenia in the district Kaliwungu, Semarang regency.The research method used in this research is quantitative correlation. The design of correlational research aims to get about the relationship between two or more research variables. The number of participants in this study were 30 people.Â Result: Support for good category families was 83.3%, family support was not 16.7%. The recurrence category of patients with mild schizophrenia was 20%, recurrence was 66.7%, weight was 13.3%. The conclusion, there was a correlation between a family and a recurrence schizophrenia in the Kaliwungu District of Semarang Regency, Therefore, for families with schizophrenia, it is hoped that they will always accompany their relatives who suffer from schizophrenia as a form of support for sufferers.